Peningkatan Hasil Tangkapan Nelayan Melalui Rekayasa Alat Bantu Berbasis Kearifan Lokal di Pesisir Sambuli. - Abdullah; Hasnia Arami; Muslim Tadjuddah; Syamsul Kamri; Naslina Alimina; Ahmad Mustafa; Indrayani, Indrayani; Sudarno (Universitas Mataram, 2025)
This research aims to increase the catch of traditional fishermen in Sambuli Village, Kendari City, by introducing and utilizing fishing aids such as coconut shell fish aggregating devices and artificial bait (jigs). The service method used is participatory action research (PAR) with the stages of socialization, training, field practice, and evaluation and mentoring. The results of the service show that coconut shell fish shelters are effective in concentrating fish, thus increasing catch productivity, while artificial bait helps to extend fishing time and location. Fishermen successfully adopted this technology independently, resulting in reduced operational costs and increased revenue. The participatory approach has proven effective in empowering fishing communities while also preserving aquatic resources. This research provides an innovative model that can be replicated for the sustainable development of traditional fisheries in other coastal regions.